A-42 Incremental Utility of Visual Assessment in Predicting Concussion Recovery Time Among Adolescents. (18th June 2020) - Sterling, J; Pardini, D; Pardini, J; Docherty, M; Mattis, J
Abstract: Objective: Sports-related concussions (SRC) often affect vision function and cognition, two components frequently assessed as part of a multimodal post-injury evaluation. The purpose of the study was to examine contributions of measures of vision function and cognition toward understanding recovery time. Method: Participants were 593 (37.6% female) adolescents ages 10–18 (M = 14.7, SD = 1.7) who were evaluated and diagnosed with a concussion within 10 days of injury. Participants were administered the King-Devick (KD) test via KD cards to assess rapid number naming speed and the ImPACT test to assess post-concussion symptoms and neurocognitive test performance. The primary outcome was number of weeks (M = 3.2, SD = 1.9) until participants were cleared to return to play by the treating physician based on a standardized protocol. Results: Poorer performance on the King-Devick test was significantly correlated with higher symptom severity (r = .41, p < .001), and poorer performance on ImPACT Verbal Memory (r = −.46, p < .001), Visual Memory (r = −.39, p < .001), Visual Motor Speed (r = −55, p < .001), and Reaction Time (r = .47, p < .001) composites. Poorer KD scores were also significantly correlated with a longer time to recovery (r = .23, p < .001). Importantly, poorer KD scores continued to significantly predict protracted recovery time after controlling for age, gender, time to initial physician evaluation, prior history of concussion, post-concussion symptom severity, and neurocognitive test performance (β = .12, p < .05). Conclusions: Performance on King-Devick testing predicted recovery time, even after controlling for important demographic/injury characteristics and cognitive testing. Evaluation of vision function is an important component of post-injury assessment for SRC.